A New Weighted T − X Perks Distribution: Characterization, Simulation And Applications - N. Ugwu, Dorathy; I. Onyeagu, Sidney; P. Igbokwe, Chinyere (Optimality, 2024)
In this article, a new distribution is proposed to innovate the Perks distribution by altering its functional form without introducing additional parameter. The proposed distribution is named a new weighted T-X Perks (WT-XP) distribution. For this distribution, expressions for some mathematical properties are derived. The maximum likelihood estimates of the parameters α and β are derived and implemented for complete samples that follow the WT-XP distribution. To illustrate the importance of the proposed distribution over the other well-known distributions, two applications to real data sets are analyzed and the WT-XP distribution appear more attractive based on the Kolmogorov Smirnov statistic p-values and the model performance indicators used.